Treponema denticola: A teammate in periodontal progression - Nymphea Pandit; Shalini Gugnani; Divya Sushil; Deepika Bali (Wolters Kluwer Medknow Publications, 2016)
There is compelling evidence that treponemes are involved in the etiology of several chronic oral diseases, including chronic periodontitis and other forms of periodontal disease. Treponema denticola suppresses fibroblast proliferation, enhancement of collagen phagocytosis by gingival fibroblasts, and the activation of both the classic and the alternative pathways of human complement. It was further shown to perturb actin regulating pathways in host cells. Recent advances, especially in molecular-based methodologies, have greatly improved our knowledge of this bacterium and its role in disease. An electronic and manual search based on agreed search phrases between the primary investigator and a secondary investigator was performed for the literature review until the year 2014. PubMed/MEDLINE databases were searched for studies to identify appropriate articles in relation to T. denticola and its virulence factors. The articles that were identified by this systematic review (total of 150) were analyzed in detail, which included the study of inference and conclusion. Within the limits of this systematic review, it can be concluded that T. denticola induces immune inflammatory response in periodontitis subjects. Procedures for gene inactivation provide a basis for characterizing the virulence factors of T. denticola, and thereby establishing its role as a teammate with other virulent plaque microorganisms in the process of tissue destruction.